Onomatopeiak Erroibarko hizkeran - Ibarra Murillo, Orreaga (Huarte de San Juan. Filología y Didáctica de la Lengua, 2011)
In this article we analyze the onomatopoeias of the Basque dialect of the Erro Valley. Some of these are also common to other dialects, some others, however, are specific to it. In this paper we present a classification of onomatopeias into semantic fields. This taxonomy rating includes sounds, nicknames, movements and objects that make noises, animals and with things of little value, games, as well as onomatopoeias associated with eating and with children’s speech. These onomatopoeias are illustrated both by means of examples in phrases or with a translation.